Effect of melatonin on visceral fat deposition, lipid metabolism and hepatic lipo‐metabolic gene expression in male rats. Issue 4 (23rd January 2021) - Wang, Linfeng; McFadden, Joseph W.; Yang, Gaiqing; Zhu, Heshui; Lian, Hongxia; Fu, Tong; Sun, Yu; Gao, Tengyun; Li, Ming
Abstract: Melatonin (MT) influences lipid metabolism in animals; however, the mechanistic effect of melatonin on liver fat and abdominal adipose deposition requires further clarity. In order to study the effects of melatonin on lipid metabolism, and hepatic fat and abdominal adipose deposition in animals, twenty Sprague–Dawley (SD) rats of 6 weeks of age with similar bodyweight were randomly divided into two groups: control (CTL) and MT‐treated (10 mg/kg/day). During a 60‐day experiment, food intake and bodyweight were measured daily and weekly respectively. At the end of treatment, blood samples were collected to collect plasma to quantify hormones and metabolic indicators of lipid metabolism. In addition, organ and abdominal adipose depots including liver, and omental, perirenal, and epididymal fat were weighed. Liver tissue was sampled for sectioning, long‐chain fatty acid (LCFA) quantification, and gene chip and Real‐time quantitative PCR (qPCR) analyses. The results showed that liver weight and index (ratio of liver weight to body weight) in MT group reduced by 20.69% and 9.63% respectively; omentum weight and index reduced by 59.88% and 54.93% respectively, and epididymal fat weight reduced by 45.34% ( p  = 0.049), relative to CTL. Plasma lipid indices, triglyceride (TG), high‐density lipoprotein (HDL), low‐density lipoprotein (LDL) and total cholesterol (TC) with MT treatment decreased significantly compared with the control. Fat and 8 LCFA content in liver in MT group also decreased. Gene chip and qPCR demonstrated that there were 289 genes up‐regulated and 293 genes down‐regulated by MT. Further analysis found that the mRNA expression of lipolysis‐related genes increased, while the mRNA expression of lipogenesis‐related enzymes decreased ( p  < 0.05) with MT. This study concluded that melatonin greatly affected fat deposition, and hepatic LCFA supply and the expression of genes associated with lipogenesis and lipolysis.